Televisão, infância e educação: os programas infantis Vila Sésamo, Sítio do Pica-Pau Amarelo e TV Colosso - Gonçalves , Francielle Sthefane Bruschi Cordeiro (2015)
Since their early history, television and the media as a whole follow the children’s lives. Initially presenting programs aimed exclusively to adults, the media became a motivating factor of family life, so that children have also become the target audience. In this study, the concepts of child and childhood are taken as social, historical and cultural concepts; therefore, it is of utmost importance to problematize them in order to understand the television influence on children. With the analysis of three programs in different historical moments – Sítio do Pica-Pau Amarelo (Yellow Woodpecker Farm), Vila Sésamo (Sesame Street) and, as a counterpoint, TV Colosso –, the aim is to examine, in the space-time of three decades, how children’s television programs were broadcast, especially in open television. This study addresses the technical aspects of media language and social importance of television in the education of subjects. Children’s programming is therefore a source for understanding the changes and social contradictions experienced in the childhood. Among the categories addressed are television programs, media language, commercial products and children’s consumption, permeated by the concept of childhood and child disseminated through the themes and approaches of the three programs analyzed. Research is based on several sources, such as literature, videos, songs, interviews, testimonials and questionnaires applied to actors who participated in the creation of these programs, based on information and contacts provided by Globo Universidade, among other sources, such as magazine and newspaper articles.